2018
DOI: 10.1109/tdei.2018.007213
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous plasma temperature at supercritical phase of pressurized CO<inf>2</inf> after pulsed breakdown followed by large short-circuit current

Abstract: The relation between breakdown characteristics and plasma temperature of a pulsed arc discharge in highly pressurized CO2 was investigated up to a supercritical phase. A transient arc discharge was generated by applying nanosecond pulsed voltage with a rising rate of 0.7 kV/ns to a point-to-plane gap of 1 mm. The breakdown voltage, arc current, and consumption energy increased with the CO2 density in the gas phase. However, they were constant at the CO2 densities in the supercritical phase. The plasma temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Kato et al reported formation of plasma and breakdown of CO 2 in PLA in scCO 2 over a short timescale of few hundred nanoseconds after the laser pulse hit the target and observed generation of cavitation bubble at 5 μs and its collapse at around 100 μs [37]. The plasma temperature depending on the CO 2 pressure has been reported to be 3873 °C-4873 °C by Maehara et al [38] and 8273 °C-12273 °C by Furusato et al [39]. The high temperature of plasma decomposes CO 2 into atomic oxygen [37,39], carbon ions and radicals [37] and carbon monoxide positive ions CO + [39].…”
Section: Resultsmentioning
confidence: 97%
“…Kato et al reported formation of plasma and breakdown of CO 2 in PLA in scCO 2 over a short timescale of few hundred nanoseconds after the laser pulse hit the target and observed generation of cavitation bubble at 5 μs and its collapse at around 100 μs [37]. The plasma temperature depending on the CO 2 pressure has been reported to be 3873 °C-4873 °C by Maehara et al [38] and 8273 °C-12273 °C by Furusato et al [39]. The high temperature of plasma decomposes CO 2 into atomic oxygen [37,39], carbon ions and radicals [37] and carbon monoxide positive ions CO + [39].…”
Section: Resultsmentioning
confidence: 97%
“…However, studies report a very rapid formation of plasma and CO 2 decomposition over a timescale of few hundred nanoseconds upon laser irradiation, with plasma temperature between 3873 and 4873 °C 31 , 32 . CO 2 breaks down into atomic oxygen 31 , 33 , and carbon ions and radicals 31 , as a result of high plasma temperature. Hot atoms in the titanium and zinc melt can then interact with reactive species formed upon CO 2 decomposition.…”
Section: Discussionmentioning
confidence: 99%
“…A positive pulsed voltage was applied to the needle electrode made from tungsten using a magnetic pulse compression circuit (MPC3010S-25LP, Suematsu Denshi Co. Ltd). The detailed topology of the circuit was expressed in a previous study [24]. The applied voltage at the needle electrode was measured with a high-voltage probe (HV-P30, Iwatsu Co., Ltd).…”
Section: Methodsmentioning
confidence: 99%